ON A METHOD FOR DETERMINING THE NEUTRAL SURFACE OF THE LAMINATED MONOLITH COMPOSITES - RADU I. IATAN; GEORGIANA LUMINIŢA ENĂCHESCU; PAVEL GH. FLORESCU (Journal of Engineering Studies and Research)
This paper approaches the methodology for determining the neutral surface of a layered composite. It is to be neglected the spins effect on normal sectional unit load, respectively the influence of the specific linear movements when calculating the bending and torsion of the unit moments. It enables the distribution of tasks specified in the layers' level for evaluating maximum stresses and comparing them to the existing structure of the materials existing in the structure.